1991
DOI: 10.1093/ajcp/96.2.171
|View full text |Cite
|
Sign up to set email alerts
|

Fulminant Childhood Hemophagocytic Syndrome Mimicking Histiocytic Medullary Reticulosis: An Atypical Form of Epstein-Barr Virus Infection

Abstract: Ten cases of pediatric fulminant hemophagocytic syndrome, encountered between 1986 and 1989, are described. They occurred in the summer, and the patients presented with fever, jaundice, hepatosplenomegaly, pancytopenia, coagulopathy, and abnormal liver function. Bone marrow studies revealed infiltration by atypical T-lymphoid cells, rare B immunoblasts, and mature histiocytes with hemophagocytosis. Initially, histiocytic medullary reticulosis was suspected in six cases. The clinical course was characterized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(30 citation statements)
references
References 0 publications
0
30
0
Order By: Relevance
“…37,38 Tissues or freshly frozen cells were available for DNA and RNA extraction in 7 cases, including lymph nodes in 2 cases, spleen in 1 case, skin in 1 case, and bone marrow in 3 cases. As controls, 10 specimens of reactive lymphoid hyperplasia (5 cases), IM (2 cases), and nasal type NK/T-cell lymphoma (3 cases) were included.…”
Section: Patients and Tissue Samplesmentioning
confidence: 99%
“…37,38 Tissues or freshly frozen cells were available for DNA and RNA extraction in 7 cases, including lymph nodes in 2 cases, spleen in 1 case, skin in 1 case, and bone marrow in 3 cases. As controls, 10 specimens of reactive lymphoid hyperplasia (5 cases), IM (2 cases), and nasal type NK/T-cell lymphoma (3 cases) were included.…”
Section: Patients and Tissue Samplesmentioning
confidence: 99%
“…It is the aetiological agent of adult infectious mononucleosis (Henle et al, 1968;Henle & Henle, I979) and is closely associated with African Burkitt's Iymphoma (Epstein ef a]., 1964;de Th6 et al, 1978), nasopharyngea] carcinoma (Old et aI., 1966), B cell neoplasia in immunocompromised patients (Hanto et al, 1985), T cell lymphoma (Su & Hsieh, 1992) and childhood virus-associated haemophagocytic syndrome (Chen et a]., 1991).…”
Section: Introductionmentioning
confidence: 99%
“…In 1979, Risdall et al [16] first described 19 cases of VAHS, the majority being due to CMV, with VZV, HSV and EBV being the other viruses implicated. Other reports [17,18] were mainly due to EBV infection. Chen et al [17] reported 10 cases of fatal paediatric haemophagocytic syndrome where EBV infection was proven by either serology or molecular method in 7 of them.…”
Section: Discussionmentioning
confidence: 99%
“…Other reports [17,18] were mainly due to EBV infection. Chen et al [17] reported 10 cases of fatal paediatric haemophagocytic syndrome where EBV infection was proven by either serology or molecular method in 7 of them. Our case 6 was particu larly puzzling in that no bacteriological or virological cause was found and postmortem did not reveal any evi dence of lymphoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation